2010 Lippincotts nursing drug guide - Karch, Amy (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
Provides information on administering medications, types of drugs, and side effects, and lists and describes hundreds of drugs with their actions, uses, and dangers, along with specific details of concern to nurses.
Consultants -- Preface -- Anatomy of a monograph -- Guide to abbreviations -- Author's acknowledgments -- Nursing process guidelines -- Preventing medication errors -- Pharmacologic classes -- Alphabetical listing of drugs by generic name
Includes index.
Keywords: CHEMOTHERAPY